Magnetic nitrogen-doped nanocarbons for enhanced metal-free catalytic oxidation: Integrated experimental and theoretical investigations for mechanism and application - Li, H.; Tian, J.; Zhu, Z.; Cui, F.; Zhu, Y.; Duan, Xiaoguang; Wang, Shaobin (Elsevier BV, 2018)
© 2018 Elsevier B.V. Developing efficient, low-cost and environmental-friendly catalysts is of great significance for heterogeneous activation of persulfates toward strategic purification of wastewater with powerful sulfate radical based advanced oxidation processes (SR-AOPs). In this study, a three-dimensional and hierarchical nitrogen-doped magnetic carbon (Co@N-C) was developed via a facile one-pot carbonization of ZIF-67 with a green precursor of urea. Acid treatment was applied to remove the surface unstable cobalt nanoparticles (NPs) to avoid the potential leaching of toxic Co ions. Benefited from the rationally structural design of the carbon precursor and post-treatment with surface engineering, the derived Co@N-C can efficiently activate PMS for fast decomposition of bisphenol A (BPA) in aqueous solution, achieving high removal of total organic carbon (TOC) with trace cobalt leaching. The impacts of diverse reaction parameters on BPA degradation were systematically investigated. More importantly, density functional theory (DFT) calculations revealed that the entrapped Co NPs can impressively modulate the electronic states of the interacted carbon regions, giving rise to enhanced carbocatalysis with synergistic promotion of N-doping. The embedded Co NPs also afford the carbocatalysts to be magnetic for an easy recycling. Additionally, comprehensive investigations of the evolution of reactive oxygen species (ROS) on the carbonaceous materials by competitive radical scavenging tests and in situ radical trapping with advanced electron paramagnetic resonance (EPR) revealed the singlet oxygen (1O2) as the dominant ROS rather than sulfate radicals. This study proposed a facile strategy for fabricating novel hybrid nanocarbon catalysts with N-doping and magnetic property and enables new mechanistic insights into carbocatalysis in AOPs, providing a promising system for green wastewater remediation.